2020
DOI: 10.1039/d0sc04352d
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation triggers guest dissociation during reorganization of an FeII4L6twisted parallelogram

Abstract: A three-dimensional FeII4L6 parallelogram was prepared from ferrocene-containing ditopic ligands. The steric preference of the bulky ferrocene cores towards meridional vertex coordination brought about this new structure type, in which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…While the cage was redox active, addition of the guest had no effect on the redox potential. The current work, coupled with other recent studies, [15,24] strengthens the postulate that rotational flexible 1,1′‐disubstituted ferrocene ligands can be reliably used to assemble discrete, cavity containing, metallosupramolecular architectures. Due the rotational flexibility of L 4EFc a wide range of [Pd n ( L 4EFc ) 2n ] 2n+ assemblies were theoretically possible but only [Pd 3 ( L 4EFc ) 6 ] 6+ is formed quantitively.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…While the cage was redox active, addition of the guest had no effect on the redox potential. The current work, coupled with other recent studies, [15,24] strengthens the postulate that rotational flexible 1,1′‐disubstituted ferrocene ligands can be reliably used to assemble discrete, cavity containing, metallosupramolecular architectures. Due the rotational flexibility of L 4EFc a wide range of [Pd n ( L 4EFc ) 2n ] 2n+ assemblies were theoretically possible but only [Pd 3 ( L 4EFc ) 6 ] 6+ is formed quantitively.…”
Section: Resultssupporting
confidence: 80%
“…More recently, Nitschke and co‐workers detailed the formation of an [Fe 4 (L) 6 ] 8+ twisted parallelogram from 1,1′‐bis(4‐aminophenyl)ferrocene, 2‐formylpyridine and Fe(II) ions [16] . A similar outcome was achieved using a related ferrocene ligand where a diazo unit replace the imine linker.…”
Section: Introductionmentioning
confidence: 84%
“…Nitschke and co‐workers reported ionic, Fe(II)‐based cages containing four ferrocene spacer motifs [44] . The cage [ 15 ] 8+ was obtained from a neutral ditopic ferrocene spacer based ligand (L 15 ) and Fe(II) ion.…”
Section: Metal Complex Spacer Based Ligands and Its Sccsmentioning
confidence: 99%
“…[20][21][22][23] In the last several years, interesting works dealing with the preparation of Fc containing molecular cages were published. [24][25][26][27][28][29][30][31][32][33][34] From the viewpoint of the construction of these highly organized molecules, Fc offers interesting perspectives related to a dynamic flexibility of the cyclopentadienyl rings (anti or syn rotation phenomenon). Most commonly, organized molecules composed of 1,1'-disubstituted ferrocenes adopting the syn conformation were reported.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32][33][34] However, some specific Fc based ligands, such as rotationally flexible ones, [24,25,33,34] offered the possibility to construct either cage structures in which 1,1'disubstituted ferrocenes adopted the anti conformation [24,25] or intriguing low-symmetry architectures in which 1,1'-disubstituted Fc's cyclopentadienyl rings were twisted. [26] Additionally, cage products that feature a confined cavity motif were shown to incorporate some specific guest molecules, such as ptoluenesulfonate anion. [24,32] Importantly, chemical oxidation assays [26] (formation of Fc + ) revealed that redox activity is assured in such specific cage products; However, preliminary electrochemical trials suggested that host-guest inclusion process might not cause the drastic changes in redox potentials of the cage.…”
Section: Introductionmentioning
confidence: 99%